The Management Strategies for Integrated Communication Channels from the Stakeholders’ Perspective Towards the Secondary Destination Image of Ratchaburi - Saisud, Revita; Bunjongmanee, Parinya; Louang-on, Anchalee (Suan Dusit Graduate School Academic Journal, 2023)
This qualitative research was aimed (1) to study the tourism components of Ratchaburi, (2) to analyze the potential of integrated communication channels, (3) to present the management strategies for integrated communication channels from the perspective of stakeholders towards the secondary destination image of Ratchaburi. The data were collected through semi-structured interviews of 10 specific informants from government and business sectors. The data verification method was the triangulation, and the data analysis method was the content analysis, SWOT analysis and TOWS matrix. The results showed that (1) the tourism components (6As) of Ratchaburi were in line with the current tourist behavior which could access to the information through the communication technology and innovation for decision-making. In addition, the destination attractions can draw tourists of all genders and ages. (2) the stakeholders’ perspective agreed with focusing on creating opportunities for communities to earn more tourism income. But there was still a lack of integration between sectors and the issue of local and tourist behavior. (3) The maxi-maxi strategy should focus on the integration of the destination strengths of Ratchaburi through storytelling and content creation for the target market. The mini-maxi strategy should aim to develop the tourism database with technology system. The maxi-mini strategy should focus on the brand image of the agrotourism model, food city, ethnic varieties and environmental awareness. The mini-mini strategy should require the government sector to develop tourism model with social responsibility and provide digital marketing knowledge.